Aware and critical teachers of the educational action through the SWOT analysis - Francesca Anello (Ricerche di Pedagogia e Didattica, 2020)
The present contribution aims at collecting the outcomes achieved by 211 subjects, who are going to teach in primary and children’s school, who used the SWOT Analysis as a context investigation tool to plan, implement and evaluate classroom interventions. In particular, this paper analyzes and discusses the effectiveness of a training program for future teachers, attending the 3rd year of university internship, able to strengthen their critical awareness through a functional knowledge of the school environment and of pupils.The pre-experimental research, which covered nine months in the Academic Year 2017-2018, has  actually increased the performance of the sample group, consisting of undergraduate students attending the degree course in Primary Education Sciences of the University of Palermo. Although the findings concern only one experimental situation, that cannot be generalized, the results showed an appreciable increase in the critical awareness of the group of trainee teachers, who have made a careful diagnosis of the educational situation functional to their teaching planning.